2017
DOI: 10.1684/pnv.2017.0654
|View full text |Cite
|
Sign up to set email alerts
|

Mental disorders, perceived health and quality of life of older prisoners in France

Abstract: Background There is a wealth of studies of somatic and mental illness among prisoners, but little on older prisoners and their cognitive aging.Aims Our study examines the cognitive performance of older male prisoners and its effect on their perceived health and quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…In our sample, only 12% of the prisoners reported having a depressive disorder, but around 60% of the sample showed depressive symptoms to some degree as measured with the PHQ-9. This result is in line with previous works, demonstrating a high number of older prisoners being depressed (Combalbert et al, 2017;Fazel et al, 2016;O'Hara et al, 2016). Also, the correlation analysis revealed that the DemTect scores were significantly associated with the PHQ-9 scores, indicating that more cognitive symptoms are correlated with more depressive symptoms.…”
Section: Executive Functioningsupporting
confidence: 92%
“…In our sample, only 12% of the prisoners reported having a depressive disorder, but around 60% of the sample showed depressive symptoms to some degree as measured with the PHQ-9. This result is in line with previous works, demonstrating a high number of older prisoners being depressed (Combalbert et al, 2017;Fazel et al, 2016;O'Hara et al, 2016). Also, the correlation analysis revealed that the DemTect scores were significantly associated with the PHQ-9 scores, indicating that more cognitive symptoms are correlated with more depressive symptoms.…”
Section: Executive Functioningsupporting
confidence: 92%
“…Unlike in Meyer's study, where the older prisoners interviewed also talk about individual ageing problems such as incontinence [6], comments in our study often focus on access to medical services in prison, the lack of exercise and poor nutrition rather than individual physical ailments. Their mental health is, however, described in more detail, which underlines the high prevalence of mental health issues and the lack of available support that has been noted in other studies [6,31,32].…”
Section: Discussionmentioning
confidence: 84%
“…While half of patients in Profile 3 reported recurrent frequent ED use, those in Profile 1 also scored high in this regard, with most being unemployed and having low household income (<$20,000). The negative associations between poverty, unemployment, poor perceived health conditions and QoL have often been reported [ 66 , 67 ], and thus, contrary to the men in Profile 2, about a third of Profile 1 patients were living in supervised housing, which may have contributed to their lower QoL scores. Previous studies have shown that QoL may be lower among patients living in such settings, compared to those living autonomously [ 65 ].…”
Section: Discussionmentioning
confidence: 99%